2013
DOI: 10.1093/heapol/czt090
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing birth centres for childbirth: an analysis of data from a community-based prospective cohort study in Nepal

Abstract: The risk of bypassing for childbirth was high in central Nepal. Provision of quality and reliable emergency obstetric services together with well trained and competent staff at birth centres are recommended to reduce bypassing and pressure on the public hospital system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
83
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 23 publications
25
83
6
Order By: Relevance
“…Studies from Nepal (1), Tanzania (2, 3), Afghanistan (4), and Uganda (5) have shown that women often circumvent their nearest obstetric care (OC) facility for childbirth. Reports suggest that bypassing by parturients varies in different settings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies from Nepal (1), Tanzania (2, 3), Afghanistan (4), and Uganda (5) have shown that women often circumvent their nearest obstetric care (OC) facility for childbirth. Reports suggest that bypassing by parturients varies in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that bypassing by parturients varies in different settings. It can range from 41% in Pwani region, Tanzania (2), to 70% in Nepal (1). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical characteristics have been evaluated in terms of bypass percentages [6], average travel distances [7], time periods [8], and costs [9]. Bypass rates vary among areas; for example, in rural America, bypass rates were less than 40% in general [6,10,11], whereas this number was much higher in some undeveloped countries [9,12,13]. Bypass patients pay costs in terms of additional travel distances, travel time and extra financial costs, and most studies have explored why they are willing to pay these costs [14].…”
Section: Introductionmentioning
confidence: 99%